1999
DOI: 10.1038/sj.gt.3300916
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of local antitumor immunity in the liver by tumor vaccine modified to secrete murine interleukin 12

Abstract: Minimal residual lesions have been a major problem in surwith the parental cells was significantly augmented in mice gical management of cancer. We transfected M5076 with vaccinated with the IL-12 transfectant compared with the murine IL-12 gene by a retroviral vector, established a control. On the other hand, both cytotoxic activity and IFNstable transfectant secreting IL-12 and investigated its anti-␥ production of spleen cells in the M5076-vaccinated and tumor effects on a spontaneous liver metastasis murin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The ability of genetically engineered tumour cells to elicit an efficient systemic antitumour response and immune memory against challenge with parental tumour cells strongly encourages one to use them as tumour vaccines [1–5, 12, 21]. However, rejection of tumour cells engineered to release cytokine alone is not necessarily followed by establishment of systemic immunity [22].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of genetically engineered tumour cells to elicit an efficient systemic antitumour response and immune memory against challenge with parental tumour cells strongly encourages one to use them as tumour vaccines [1–5, 12, 21]. However, rejection of tumour cells engineered to release cytokine alone is not necessarily followed by establishment of systemic immunity [22].…”
Section: Discussionmentioning
confidence: 99%
“…These include the use of fibroblasts (Tahara et al, 1994;Zitvogel et al, 1995) or tumor cells (Colombo et al, 1996) transduced in vitro with IL-12 cDNA by a retroviral vector, the direct intratumoral injection of a recombinant vaccinia viral vector (Meko et al, 1995) or an adenoviral vector encoding a transgenic IL-12 protein (Chen et al, 1997;Bramson et al, 1996), and the direct intradermal or intramuscular injection of plasmid DNA expression vector encoding the IL-12 subunits (Rakmilevich et al, 1996;Tan et al, 1996). In addition to the local effect of IL-12 cDNA, some reports have demonstrated antimetastatic effects of IL-12 gene therapy in a number of murine tumor models (Caruso et al, 1996;Rodolfo et al, 1996;Lode et al, 1998;Popovic et al, 1998;Siders et al, 1998;Fuji et al, 1999;Schultz et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al showed that a predominately IFN-c response was seen in splenocytes of mice challenged with IL-12-secreting tumor and that the rejection was mediated by both CD4 þ and CD8 þ T cells, although depletion of both cell types does not completely abrogate the response [77]. In a liver cancer model, IL-12-secreting cells induced a CD3 þ , NK1 þ infiltrate [78] raising the possibility that innate responses also participate in the rejection of these IL-12-secreting tumors.…”
Section: Modification Of Tumor-cell Vaccines Expressing Cytokinesmentioning
confidence: 96%